Improving health equity: changes in self-assessed health across income groups in China - Yuqi Zhou; Xi Yao; Weiyan Jian (BMC, 2018)
Abstract Background Beginning in 2010, China has endeavoured to expand health coverage and provide residents with fair access to primary health care with the intention of improving health equity. This study aims to measure changes in income-related health inequity in China between 2010 and 2014. Methods Data were extracted from the nationally representative annual survey of the China Family Panel Studies in 2010 and 2014 with a first wave of 31,743 respondents and a second wave of 32,006 respondents over age 15. In both years, subjects were stratified into the following five categories of income: poorest 20%, lower 20%, medium 20%, higher 20% and richest 20%. The concentration curve and index was used to compare the distribution of health status in income quintiles, and a logistic model was used to examine the relationship between health and socioeconomic indicators with self-assessed health as the primary outcome of interest. Results Income was significantly associated with self-assessed health in China. The concentration curve was above the line of equality in both years, while the self-assessed health line in 2014 was closer to the equality line. The concentration index (CIN) displayed the similar result of decreasing inequality, with the CIN in 2014 (− 0.157) closer to zero (the line of equality) than that of 2010 (− 0.167). In 2010, there was a decreasing trend of people reporting poor health from the poorest to the richest, while in 2014, there was no significant difference between the poorest and lower 20% or between the higher 20% and the medium 20%. The odds ratio of the prevalence of self-reporting poor health between the poorest and richest increased from 0.555 (95% CI: 0.484-0.636) in 2010 to 0.598 (95% CI: 0.513-0.696) in 2014. Conclusions From 2010 to 2014, the self-assessed health gap between income groups in China decreased, and health equity improved. However, health differences remain. In order to achieve better health for all, China should further strengthen the role of primary care in reducing health inequity.